Analysis of Vehicle Emission Policies and Electric Vehicle Incentives on Air Pollution and Sustainable Transportation Use in Jakarta, Indonesia - Judijanto, Loso; Nugroho, Budi Sulistiyo; Annasit, Annasit; Aulia, Haris Numan; Furqon, Zami (West Science Social and Humanities Studies, 2024)
This research investigates the impact of vehicle emission policies and electric vehicle incentives on air pollution perceptions and sustainable transportation use in Jakarta, Indonesia. Through a quantitative analysis employing structural equation modeling, survey data from diverse stakeholders are analyzed to assess the relationships between key variables. Findings indicate significant associations between stringent vehicle emission policies, electric vehicle incentives, lower air pollution perceptions, and increased sustainable transportation use. These results underscore the importance of comprehensive policy measures in promoting environmental sustainability and fostering sustainable transportation practices in urban areas.